1953
DOI: 10.1007/bf02636941
|View full text |Cite
|
Sign up to set email alerts
|

Volatile decomposition products of the oxidative polymers of ethyl linolenate

Abstract: Summary Oxidative polymers which had been isolated from autoxidized ethyl linolenate were oxidatively decomposed in a closed system at room temperature. The decomposition products were collected in appropriate traps and separated into various fractions on the basis of their volatility and solubility. The aldehydes and ketones thus obtained were converted into 2,4‐dinitrophenylhydrazones, chromatographed on silica gel, and the isolated 2,4‐dinitrophenylhydrazones identified by standard procedures. Methyl ethyl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
11
0

Year Published

1958
1958
1988
1988

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 11 publications
1
11
0
Order By: Relevance
“…Trace alk-Z-enal Cs could come from linolenate, but may not have, because the major linolenate alk-2-enal Cg should also be present. Chang and Kummerow (1953) found n-alkanals CS, Cg, and Cs among the volatile decomposition products of linoleate oxidative polymers. The compound n-alkanal C5 was not detected in this study.…”
Section: And Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Trace alk-Z-enal Cs could come from linolenate, but may not have, because the major linolenate alk-2-enal Cg should also be present. Chang and Kummerow (1953) found n-alkanals CS, Cg, and Cs among the volatile decomposition products of linoleate oxidative polymers. The compound n-alkanal C5 was not detected in this study.…”
Section: And Discussionmentioning
confidence: 95%
“…Kawahara et al (1952) found alkanal C, and C3 and alk-2-enal Cg among the volatile cleavage products of oxidized linolenate. Johnson et al (1953) found methyl ethyl ketone, alkanal CZ and Ca, and alk-2-enal Cj in the products of decomposed oxidative polymers of linolenate. A compound of an apparently new class was detected in small amounts in the oxidized linolenate.…”
Section: And Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Isolation and characterization of the autoxidation products of fats and oils have been the subject of considerable research in the past decade (Badings, 1959;Brekke and MacKinney, 1950;Chang and Kummerow, 1954;Gaddis and Ellis, 1959b ;Johnson et al, 1953 ;Swift et al, 1945Swift et al, , 1949. The reagent 2,4-dinitrophenylhydrazine (DNP) forms crystalline derivatives with aldehydes and ketones, with characteristic melting points.…”
mentioning
confidence: 99%
“…Regarding the studies on stability of oils and fats, much work has ~een done (3,10,11,12,13,14,15,16 The hydroperoxides thus form~d may cleave in one or two ways yielding alkanals, alkenals, alk-dienals, dicarboxyls, alcohols, and hydrocarbons depending on the fatty acids involved (13,14,15). Thermal decomppsition of the hydroperoxides formed from unsaturated fatty acids yields about 90 percent by weight of dimeric polymers (16).…”
mentioning
confidence: 99%